ANALISIS AKTA DIBAWAH TANGAN YANG DILEGALISASI DALAM PERSPEKTIF HUKUM DI INDONESIA - Tito Widyanto Cipta; Moh. Sugiyono; Achmad Nurjannah (IAIC (Institut Agama Islam Cirebon), 2020)
The purpose of this research is to find out how the Notary's responsibility towards the legalization of underhanded deeds and how the strength of underhanded deeds that have been legalized by a Notary. The method used in this study is a normative juridical research method and it can be concluded that in article 1874 paragraph 2 of the Civil Code it is stated explicitly that signing an underhand writing is the same as affixing a thumbprint to a statement dated from a notary or other official appointed by law stating that the affixer the thumb is known to him or has been introduced to him. And an underhand deed only has the power of formal proof, that is, if the signature on the deed is recognized, it means that the statement contained in the deed is recognized and justified.